Pascal Quignard : towards the Vanishing Point - Vuong, Léa (Research monographs in French studies, 2016)
The award-winning writer Pascal Quignard (1948-) has published many texts and has collaborated with painters, musicians and filmmakers. Yet despite the popularity and critical recognition of his work, Quignard remains a discreet and fleeting presence in the current cultural landscape, sharing with other contemporary French writers the belief that literature is a form of self-effacement. In this first critical study in English, Léa Vuong offers a comprehensive survey of Quignard's still growing œuvre by examining his specific attempts to produce disappearance through -- and for -- writing. His texts and collaborations appear as vanishing acts where the writer, like the figure on the Tomb of the Diver found in Paestum, remains suspended between presence and absence.